Análise funcional do papel da enzima DNA metiltransferase 2 (DNMT2) no desenvolvimento e resposta à estresses e identificação e caracterização de fragmentos derivados de tRNA (tRFs) em Arabidopsis thaliana - Rosa, Cristiane de Santis Alves [UNESP] (2015)
DNA methylation is associated with genetic regulation, cell memory, silencing of transposable elements, genomic imprinting and repression of pseudo-elements coming from duplicate sequences. Methylation patterns are established, kept and translated via an appropriate functional DNA methylation machinery, which includes a family of proteins classified into three methyltransferase enzyme groups: DNMT1, DNMT3 e DNMT2. DNA methyltransferase 2 (DNMT2) was first identified by searching for novel DNA methyltransferase candidates. DNMT2 is highly conserved in different kingdoms and does not have a biological function well defined so far; however, it has been shown that DNMT2 can methylate both DNA and RNA in animal cells, most specifically transfer RNA (tRNA). In human cells, DNMT2 is localized both in the nucleus and in the cytoplasm, being capable to migrate from nucleus to cytoplasm under stress conditions. In the cytoplasm, DNMT2 methylates tRNAs, possibly to protect against cleavage events that occur under stress conditions. When these cleavages occur in a specific pattern, small RNA fragment emerges (tRFs). tRFs are found in several species, including Arabidopsis thaliana. It seems that these tRNA fragments are part of a new RNAi pathway. However, its biological role has not been reveal yet. The aim of this work is to evaluate the possible role(s) of DNMT2 in plant development and stress response and also establish its possible role in tRNA protection. So far we demonstrated that AtDNMT2 has both nuclear and cytoplasmic cellular localization and can also be visualized in what seen to be the cytoskeleton. We determined that AtDNMT2 does not play role in tRNA AspGTC protection under oxidative stress, though AtDNMT2 is up regulated in different stresses. The mutant plant Atdnmt2 does not have obvious phenotype, what makes harder to understand its biological role, leading us to deeper molecular studies. In this context, the present work reveals...